Gamelan dalam Citra Budaya Popular : Studi Kasus Lokananta Gamelan Gigs di Surakarta, Jawa Tengah - Suciati; Muhammad Nur Salim (Program Studi Pendidikan Musik FBS UNP, 2025)
Purpose: This article aims to describe an event titled Lokananta Gamelan Gigs (LOGIGS), which is regularly held at Lokananta, Surakarta. The event was initiated to address a specific issue: the lack of interest among younger generations, particularly Gen Z, in traditional gamelan arts. To tackle this challenge, the organizers developed strategies to package and promote LOGIGS using a popular culture approach, aiming to spark greater interest in gamelan among young people. Additionally, social aspects, including the importance of collectivism to create an inclusive space within the gamelan community, also form a critical foundation of the event's objectives. This emphasis on collectivism and inclusivity is expected to foster better management skills and increased productivity within the gamelan scene. Methods: This research employs a qualitative method, integrating art studies, cultural studies, management, and ethnography. Data were gathered through Instagram content analysis, media news reviews, direct observations of performances, and interviews. Results and Discussion: Findings reveal that LOGIGS adopts a popular culture approach to realize its vision, as reflected in various elements such as poster design styles, performers' attire, and other subcultural aspects, as well as the event’s overall presentation. LOGIGS also functions as an inclusive space and an educational platform, evident in Instagram posts discussing gamelan knowledge. Conclusion: The implementation of LOGIGS through a popular culture approach highlights an innovative gamelan event management model that has not been explored in prior discussions.